2008
DOI: 10.1016/j.ces.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Second-order statistical regression and conditioning of replicate transient kinetic data

Abstract: A new method has been developed to estimate physico-chemical parameters from transient kinetic data: second-order statistical regression (SOSR). It allows to account for heteroskedasticity and nonwhiteness of the noise in the time series measured. SOSR makes use of replicates to estimate the second-order statistics, i.e. the autocovariance pattern of the noise. A sample principal noise component analysis of the experimental time series allows nonlinear least-squares (NLSQ) regression of the latter. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Roelanta et al [18] suggested a nonlinear least square method of preconditioning transient experiments containing time-series replicates based on systems of partial differential equations such as the one presented in this paper. Alternatively, the time series replicates may be averaged and regressed; this follows important assumptions that the noise is normally distributed amongst the replicates and that the independent time variable has no experimental error associated with it (automated data acquisition is thus recommended).…”
Section: Determination Of Diffusion Coefficient From Experimental Datamentioning
confidence: 98%
See 2 more Smart Citations
“…Roelanta et al [18] suggested a nonlinear least square method of preconditioning transient experiments containing time-series replicates based on systems of partial differential equations such as the one presented in this paper. Alternatively, the time series replicates may be averaged and regressed; this follows important assumptions that the noise is normally distributed amongst the replicates and that the independent time variable has no experimental error associated with it (automated data acquisition is thus recommended).…”
Section: Determination Of Diffusion Coefficient From Experimental Datamentioning
confidence: 98%
“…The mathematical expression of J AVG is obtained by combining the expressions for J in and J out given by Eqs. (18) and (10), respectively:…”
Section: Determination Of the Permeability Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…31,148,149 Analytical advances specific to the TAP methodology have also been reported. 146,[150][151][152][153][154] Since 2001 a step-by-step advancement of the mathematical theory of the TAP "reaction-diffusion" systems has been constructed, including:…”
Section: Discussionmentioning
confidence: 99%
“…Section 2.1 gives the detailed mathematical background and Section 2.2 gives some examples of this directly-implementable theory. The interested reader can find another application in Roelant et al [2] , [3] .…”
Section: Datamentioning
confidence: 99%